Binary mixture convection in a horizontal channel under the Soret effect action - Stepanova Irina (Theoretical and Applied Mechanics)
The mathematical model describing stationary flow of binary liquid mixture is under consideration. The exact solution of the equations of convective heat and mass transfer is constructed for the special form of the functions of temperature and concentration. All possible statements of boundary value problems are studied in order to analyse thermal diffusion separation of binary mixture in a long horizontal channel with rigid walls. It is discovered that only one of the statements (at inhomogeneous heating of both rigid walls) leads to feasible results. With the help of the constructed solution for the mentioned boundary value problem the effect of layer thickness, given flow rate and action of gravity force on the separation process, is analysed.